Environmental Biomonitoring: The Possibility of Using Preserved Biological Specimen - Lau, Seng; Pei Sun, Loh (UKM Publisher, 2001)
Environmental monitoring has become a very important tool in environmental management. However, it is very frequent that some important data on the initial status or conditions of a particular area is not available. This obstructs efforts to rehabilitate a disturbed area or to determine the changes that have taken place over a specific period of development. Biological sampling has been widely practiced by biologists over centuries and it is more likely to find preserved biological specimen of a particular area in museums and laboratories. This paper is to explore the possibility of using the preserved biological specimen to determine/estimate the historical environmental status of the area. The research was conducted using freshwater molluscs collected from Bau District in Sarawak. The samples collected at each site were divided into two portions, one would be analysed for heavy metals immediately while the other portion was preserved in methanol for 6 months before the chemical analysis. The results showed that the metals contents in the tissue of the molluscs differ significantly between the fresh and preserved specimen. However, the contents of metals in the shell of the animals did not indicate any significant variation. The variation of metal contents in the tissues may be related to the solubilisation of fatty tissues by methanol thus causing the metal content to increase per unit weight of the dried tissue. This paper concludes that there is a possibility of using preserved samples for biomonitoring of the earlier environment, however much work on the validation and this approach need to be done.